TRI HITAKARANA DALAM UPACARA TANJUNG SARI DESA DLIMAS KECAMATAN CEPER - Sugiman (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2019)
Tri Hitakarana in the Tanjung Sari Ceremony in the Klaten Dlimas Village. This ritual allegedly appeared in the 10th century. Starting from a relative of the Mataram palace, Ki Dlimas, who carried out a spiritual journey to Klaten. He stopped and rested until he fell asleep under the tree of five that had golden yellow fruit. For the magical message from a beautiful woman named Nyi Rara Tanjung Sari, that place was to be called the Dlimas. This message was followed by Ki Dlimas. Since then the Dlimas region has been inhabited by many residents. When the 4th Ki Dlimas descendant Ki Demang Rawatmeja came to power there, a terrible epidemic broke out. Many residents and maintenance animals died. Hamlet Dlimas became lonely. Ki Demang Rawatmeja then meditated to ask for God's guidance. At that time, two beautiful women, Nyi Rara Tanjung Sari and Nyi Rara Payung Gilap, were met by magic. They ordered to look for people who want to live in Dlimas. They both want to be protective citizens but every year on Friday Kliwon or Friday Wage in Sura must caos offerings. Clean rituals at Tanjung Sari Village are performed by all residents. Ahead of the Celebration a committee was formed. They are tasked with coordinating activities, ranging from the arrangement of events, budget plans, collecting dues of citizens to design community service activities, decorating buildings and pepunden ceremony ceremonies, preparing arts, decoration, security, cleanliness of residential neighborhoods, to the top of events, and post worship including committee responsibilities. This ritual serves as a unifying citizen of Dlimas Village, who for a year was preoccupied with the tasks carried out in his workplace. Performing arts are also included in the ceremony. Religiosity of religious teachings is formulated specifically in the form of art, thus helping the process of understanding. At the ceremony they gathered together to restore the social ties that had slack. This is all for the sake of increasing unity, unity and sense of social solidarity. The meaning of the ceremony strengthens their religious life which is built from a sense of togetherness, inhales the power of the universe and relies on belief in pepunden and God so that they are blessed with harmony, peace and prosperity.